Environmental Experiences of Chinese People in the Mid-Nineteenth Century Australian Gold Rushes. (1st January 2011) - Sheng, Fei
Abstract : The migration of Chinese people to Australia was part of a global migration that occurred around 1850, stimulated by gold discoveries around the Pacific Rim. The research analyzes the deep ecological factors in China that spurred the migration at a time when the discovery of gold as a natural resource in Australia made the country an ideal migration destination. The author shows how the Chinese migrants applied their native environmental experience in a white settler colony. Through unique mining methods and market gardening, the Chinese transformed the indigenous landscape and shaped their "New Gold Mountain" in Australia. Although the Chinese environmental experience benefited both themselves and other migrants, there were also negative effects. Environmental cooperation was eclipsed by environmental conflicts between Chinese and white miners. Both cultural and natural factors limited the spread of Chinese environmental experiences in the Australian gold rushes. The Chinese environmental experience in the Australian context was also a result of existing racist policies. Within a broader perspective, the paper demonstrates how different migrants interacted with the indigenous environment and with each other